Marine oils - stabilization, structural characterization and omega-3 fatty acid concentration - Wanasundara, Udaya Nayanakantha, 1960- (1996)
Thesis (Ph.D.)--Memorial University of Newfoundland, 1997. Biochemistry Bibliography: leaves [252]-282